Multipurpose Bench as an Alternative Infrastructure of Transportation - Sandi Yudha; Ihsan Ihsan; Nuzuli Fitriadi (Jurnal Inotera, 2019)
Sitting is one of the rest activities carried out by humans to restore energy when tired of doing activities and a bench is an infrastructure that humans use to sit when they unwind. The most important factor for bench design is a convenience for its users. While the table is an infrastructure that is used by humans to carry out writing, eating and so on. Combining bench and table concepts into one, it is very necessary to summarize the place according to its function. The literature study on this design gave rise to a new design in which a multifunctional bench is not only useful for sitting but also functions to carry out activities that require a desk.